2007
DOI: 10.1016/j.biopsych.2006.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressant-like Activity of the Fatty Acid Amide Hydrolase Inhibitor URB597 in a Rat Model of Chronic Mild Stress

Abstract: Background:The endocannabinoid anandamide may be involved in the regulation of emotional reactivity. In particular, it has been shown that pharmacological inhibition of the enzyme fatty acid amide hydrolase (FAAH), which catalyzes the intracellular hydrolysis of anandamide, elicits anxiolytic-like and antidepressant-like effects in rodents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

32
255
4
7

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 315 publications
(300 citation statements)
references
References 56 publications
(88 reference statements)
32
255
4
7
Order By: Relevance
“…Notably, in our experiments, neither URB597, JZL184, nor combo treatment reversed the depression-like behavior observed in CUS mice. Although the anti-depressant properties of URB597 (Bortolato et al, 2007) and JZL184 (Zhong et al, 2014) in stress-exposed rodents have been reported, several factors (animal species, type of behavioral test, duration and type of stressors, design of treatment, dose of drugs) may explain the Endocannabinoid system modulation of stress-induced pain E Lomazzo et al discrepancy between our data and previous studies. Further investigations should shed light on these differences in efficacy of treatments.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…Notably, in our experiments, neither URB597, JZL184, nor combo treatment reversed the depression-like behavior observed in CUS mice. Although the anti-depressant properties of URB597 (Bortolato et al, 2007) and JZL184 (Zhong et al, 2014) in stress-exposed rodents have been reported, several factors (animal species, type of behavioral test, duration and type of stressors, design of treatment, dose of drugs) may explain the Endocannabinoid system modulation of stress-induced pain E Lomazzo et al discrepancy between our data and previous studies. Further investigations should shed light on these differences in efficacy of treatments.…”
Section: Discussioncontrasting
confidence: 99%
“…Consistent with previous reports (Bortolato et al, 2007), CUS did not affect the basal level of AEA (Figure 4), 2-AG ( Figure 5), and PEA (Supplementary Figure 2) in any of the tissues examined. Nevertheless, in the serum of vehicle-treated CUS mice a decrease in AEA (Figure 4g) and PEA (Supplementary Figure 2g) was observed as compared with controls, although it was not statistically significant (p ¼ 0.2).…”
Section: Determination Of Endocannabinoid Levelssupporting
confidence: 93%
See 3 more Smart Citations